1998
DOI: 10.1007/s100529800756
|View full text |Cite
|
Sign up to set email alerts
|

Double $Q^2$ -rescaling model and the nuclear effect of the parton distribution functions

Abstract: In order to overcome the shortcoming of nonconservation of nuclear momentum existing in the original Q 2 -rescaling model(OQ 2 RM) and avoid introducing nuclear shadowing factor, we proposed a double Q 2 -rescaling model(DQ 2 RM) for the parton distributions of the bound nucleon. Using the experimental data of lepton-nucleus deep inelastic scattering(DIS) and the condition of the nuclear momentum conservation, the Q 2 -rescaling parameters of various partons for Sn, Fe, Ca and C nuclei are determined.The resca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…[ 24,32 ] The hepatoprotective effects of OA allow its use in China as an over‐the‐counter oral drug for liver disorders such as viral hepatitis in humans. [ 25,33–35 ] A recent study reported that neonatal intake of OA prevented and attenuated the subsequent development of high fructose diet‐induced NAFLD in rats. [ 36 ] We have also shown that OA diminished liquid fructose‐induced fatty liver in rats and demonstrated that OA‐elicited lipid‐lowing action is associated with selective regulation of hepatic SREBP1c‐mediated expression of various genes, including Scd1 , which is responsible for de novo FA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24,32 ] The hepatoprotective effects of OA allow its use in China as an over‐the‐counter oral drug for liver disorders such as viral hepatitis in humans. [ 25,33–35 ] A recent study reported that neonatal intake of OA prevented and attenuated the subsequent development of high fructose diet‐induced NAFLD in rats. [ 36 ] We have also shown that OA diminished liquid fructose‐induced fatty liver in rats and demonstrated that OA‐elicited lipid‐lowing action is associated with selective regulation of hepatic SREBP1c‐mediated expression of various genes, including Scd1 , which is responsible for de novo FA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…It became clear that even in a DIS process characterized by high locality of the probe-target interaction region, a different picture emerges from the nucleus other than a collection of quasi-free nucleons. On the theory side, despite decades of theoretical efforts [2,3,4,5,6] with increased sophistication, a unifying physical picture of the origin of the EMC effect is still a matter of intense debate. To reach the next level of our understanding of nuclear QCD and unravel the partonic structure of nuclei, experiments need to go beyond the inclusive measurements and focus on exclusive and semi-inclusive reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Hard exclusive experiments such as Deep Virtual Compton Scattering (DVCS) and Deep Virtual Meson Production (DVMP) provide an important new probe that will allow us to discern among the different interpretations of nuclear effects on the structure of embedded nucleons in the nuclear medium. By introducing a new framework to describe both the intrinsic motion of partons and their transverse spatial structure in nuclei [4,5,6,7,8,9]. valuable information can be obtained from the measurement of the nuclear Generalized Parton Distributions (GPDs) representing the soft matrix elements for these processes.…”
Section: Introductionmentioning
confidence: 99%